2016
DOI: 10.1183/16000617.0038-2016
|View full text |Cite
|
Sign up to set email alerts
|

Sports related to drowning

Abstract: Aquatic sports are included in the top list of risky practices as the environment per se carries a possibility of death by drowning if not rescued in time. Not only are aquatic sports related to a high risk of death, but also all sports practiced on the water, over the water and on ice. Whatever the reason a person is in the water, drowning carries a higher possibility of death if the individual is unable to cope with the water situation, which may simply be caused by an inability to stay afloat and get out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…TM rupture occurs when a surfer’s ear is hit directly by the tip of a large wave or when the ear slaps the water surface after a high-speed wipe-out 6. A surfer’s risk of drowning injuries would theoretically increase following TM rupture in large surf, as it would cause disorientation and hamper attempts when surfacing 37. TM rupture is a cause of conductive hearing loss,38 while conductive hearing loss may occur in up to 20% of mild traumatic brain injuries 39.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TM rupture occurs when a surfer’s ear is hit directly by the tip of a large wave or when the ear slaps the water surface after a high-speed wipe-out 6. A surfer’s risk of drowning injuries would theoretically increase following TM rupture in large surf, as it would cause disorientation and hamper attempts when surfacing 37. TM rupture is a cause of conductive hearing loss,38 while conductive hearing loss may occur in up to 20% of mild traumatic brain injuries 39.…”
Section: Resultsmentioning
confidence: 99%
“…Watson et al reported 11 cervical spine injuries in more than 2400 drownings 68. Although surfers would likely make up a small proportion in these studies and on average be stronger swimmers, it suggests that routine immobilisation of the cervical spine in unconscious surfers, without assessing signs of a traumatic injury, is contraindicated as it may delay vital cardiopulmonary resuscitation and possibly lead to death 37 64 69. Thus, it is imperative that first responders understand and recognise the patterns of head and neck trauma to ensure the correct recognition and appropriate management of these injuries.…”
Section: Overuse Conditionsmentioning
confidence: 99%
“…The net effect is to blow off carbon dioxide to a level where the drive to breathe and self-protect is blunted. (Szpilman, 2016) Even the American Red Cross has defined shallow-water blackouts in terms of hypoxia, "where alternative causes of unconsciousness have been excluded". (Bart, 2020) It is not clear from the text if one of the "alternative causes of unconsciousness" that was excluded was CO2 narcosis.…”
Section: Upes and Diving Physiologymentioning
confidence: 99%
“…Physicians need to recognize these situations to treat them appropriately. Drowning that is secondary to other primary insults can be classified as 24 :…”
Section: Secondary Drowningmentioning
confidence: 99%